2001
DOI: 10.1021/ma000968f
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Morphology of Phase-Separating Polymer Blends

Abstract: Simulations of phase separation under oscillatory shear flow have been performed based on the time-dependent Ginzburg-Landau (TDGL) equation. To calculate the stress tensor, the expression proposed by Kawasaki was used. The results of the simulations have been confronted directly with experimental results on a LCST blend of PRMSAN/PMMA to evaluate the potential of the simulations. The effect of quench depth, shear amplitude, and shear frequency on the morphology development as well as on the corresponding rheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 40 publications
7
72
3
Order By: Relevance
“…In other case, the structure is declared as cocontinuous only It has been reported that the frequency dependence of the loss modulus G" of the blend with the bicontinuous structure is also expressed by the power law G" ~ w m with the exponent m somewhat smaller than n. [25][26][27][28] The same result is obtained in the present study, although the reason for m < n is not known.…”
Section: The Bicontinuoussupporting
confidence: 85%
See 1 more Smart Citation
“…In other case, the structure is declared as cocontinuous only It has been reported that the frequency dependence of the loss modulus G" of the blend with the bicontinuous structure is also expressed by the power law G" ~ w m with the exponent m somewhat smaller than n. [25][26][27][28] The same result is obtained in the present study, although the reason for m < n is not known.…”
Section: The Bicontinuoussupporting
confidence: 85%
“…[25][26][27][28][29] The reported exponent n is in the rage of 0.5 < n ≤ 1. However, in all these reports, detailed study on the phase separated structure is missing.…”
Section: The Bicontinuousmentioning
confidence: 99%
“…[18][19][20][21] The behavior similar to the percolation threshold, G' ∼G" ∼ω n with tanδ = tan(nπ/2), was also observed 22) . However, these behaviors are somewhat vague due to the coarsening of bicontinuous structure during rheological measurement and to possible acceleration of domain growth (or break up) affected by small (or large) amplitude oscillation.…”
Section: Resultsmentioning
confidence: 54%
“…Representative Institution number [1] V. Altstädt Until 1995: BASF, Ludwigshafen, Germany; 1995-2000: TU Hamburg-Harburg, Hamburg, Germany; Since 2000: University Bayreuth, Bayreuth, Germany [2] L. Glas Shell, Ottignies Lovain la Neuve, Belgium [3] B. Pukánszky TU Budapest, Budapest, Hungary [4] D. W. Schubert GKSS, Geesthacht, Germany [5] G. H. Michler University Halle-Wittenberg, Merseburg, Germany J. Laatsch [6] R. Moore ICI Technology, Middlesbrough Cleveland, England [7] J. G. Williams Imperial College, London, UK [8] F. Ramsteiner BASF, Ludwigshafen, Germany…”
Section: Laboratorymentioning
confidence: 99%
“…In a paper by V. Schytt and J. Lyngaae-Jørgensen [2], the limits of miscibility in the quiescent state and during flow has been discussed. I. Vinckier and H. M. Laun reported the manifestation of the interface in oscillatory shear measurements [3,4], and Z. I. Zang, Y. L. Yang, I. Vinckier, and H. M. Laun compared, measured, and simulated morphologies under oscillatory shear [5]. D. W. Schubert investigated the χ-parameter and the phase diagram of PαΜSAN/PMMA blends by cloudpoint and neutron-scattering techniques [6].…”
Section: Historic Backgroundmentioning
confidence: 99%